THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP OF ADMINISTRATOR AND ORGANIZATION CULTURE OF SPECIAL EDUCATIONAL SCHOOL FOR STUDENT WITH INTELLECTUAL DISABILITIES NORTHERN REGION, BUREAU OF SPECIAL EDUCATION ADMINISTRATION - คำชา รำพัน (Pathumthani University Academic Journal, 2020)
The purposes of this descriptive research were 1) to study Transformational Leadership of Administrator at of Special Education al School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration. 2) to investigate the Organization Culture of Special Educational School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration 3) To find the relationship between Transformational Leadership of Administrator and Organization Culture of Special Education al School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration. The sample comprised 196 teachers who work at Special Educational School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration. Multistage random samplings were use. The research tools comprised three sets of questionnaires, covering personnel data, Transformational Leadership and the Organization Culture. They were tested for reliability and validity. The reliability of the second set were .71 and the third sets were .71. The statistical devices used for data analysis were both descriptive statistics (frequency, percentage, mean, and standard deviation) and Pearson product-moment correlation coefficient. The findings were as follows. 1) The Transformational Leadership of Administrator at of Special Education al School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration at highest level. 2) The Organization Culture of Special Education al School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration at highest level. Finally, 3) There was statistically significant positive correlation between Transformational Leadership of Administrator and Organization Culture of Special Education al School for Student with Intellectual Disabilities Northern Region, Bureau of Special Education Administration at medium level (r= .54) p < .01.